La legge organica della giustizia riparativa e il ruolo della vittima nella riforma Cartabia: luci e ombre - Francesca Di Muzio (Rivista di Criminologia, Vittimologia e Sicurezza)
The Cartabia’s reform, within the Title IV on restorative justice, will serve as a testing ground for this model of justice to suit its different versions, as a true Copernican revolution for the criminal justice system because this would challenge the theories of punishment. Within the context of the criminal proceedings reform, the challenge for justice will be to repair the crimes. This article serves to develop contents to answer these questions: which crimes? Which choice should be done to guarantee the best interest of the victims to avoid the risks of secondary victimization?